Resource Competence Development for State Apparatus as an Improvement Effort Quality of Public Services - Saleh, Choirul; Puspitasari, Novi (Socious Journal, 2025)
Improving the competencies of state apparatus resources is essential for enhancing the quality of public services, which is crucial for fostering public trust in government and creating an effective and responsive state. This research explores the approaches and strategies used to develop competencies among state apparatus resources and analyzes their impact on public service quality. Employing a qualitative approach, the study examines the classification, developmental steps, quality of outcomes, and supportive factors influencing competency enhancement at the State University of Brawijaya, Malang, Indonesia. The findings reveal key strategies for fostering competencies that align with contemporary demands, including targeted training programs and institutional support mechanisms. These efforts contribute to improving public service delivery and supporting national development. The study offers insights into competency development in higher education settings, highlighting its role in advancing public service quality and reinforcing the nation's progress